The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-28809-9
|View full text |Cite|
|
Sign up to set email alerts
|

Revealing the complex genetic structure of cultivated amaryllis (Hippeastrum hybridum) using transcriptome-derived microsatellite markers

Abstract: Although amaryllis (Hippeastrum hybridum) plants are commonly used in physiological and ecological research, the extent of their genomic and genetic resources remains limited. The development of molecular markers is therefore of great importance to accelerate genetic improvements in Hippeastrum species. In this study, a total of 269 unique genes were defined that might regulate the flower spathe development of amaryllis. In addition, 2000 simple sequence repeats (SSRs) were detected based on 171,462 de novo as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Except for Me03/Em11 and Me06/Em07, all primer combinations showed 100% polymorphism across the accessions. In previous studies, RAPD, ISSRs and SSRs have been used to analyze the genetic variation in 25, 62 and 104 amaryllis hybrids [7][8][9][10]. However, the percentage of polymorphic fragments found in the RAPD (72.6%), ISSRs (92.4%) and SSRs (93.9%) was lower than that in the SRAPs (99.5%) in our study.…”
Section: Resultscontrasting
confidence: 69%
See 3 more Smart Citations
“…Except for Me03/Em11 and Me06/Em07, all primer combinations showed 100% polymorphism across the accessions. In previous studies, RAPD, ISSRs and SSRs have been used to analyze the genetic variation in 25, 62 and 104 amaryllis hybrids [7][8][9][10]. However, the percentage of polymorphic fragments found in the RAPD (72.6%), ISSRs (92.4%) and SSRs (93.9%) was lower than that in the SRAPs (99.5%) in our study.…”
Section: Resultscontrasting
confidence: 69%
“…The average values of H and I for all SRAP primer combinations were 0.344 and 0.513, respectively. In the SSR study with more germplasm, the average H and I values in 104 cultivated amaryllis were 0.264 and 0.407, respectively [10]. Overall, these results confirmed that SRAP markers can be powerful and effective tools for clarifying genetic diversity in cultivated amaryllis.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Amaryllis is a genus from the family Amarylidaceae and the order Asparagales. The genus contains 75 species South America (Wang et al, 2018), and its endemic species are found in Brazil. It is a bulbous plant among the top 20 popular flowers in the world.…”
Section: Introductionmentioning
confidence: 99%